High step‐up high step‐down bidirectional DC/DC converter. Issue 12 (18th August 2017) - Babaei, Ebrahim; Saadatizadeh, Zahra; Cecati, Carlo
Abstract : In this study, a new high step‐up high step‐down bidirectional dc–dc converter is proposed. In the proposed converter, the voltage conversion ratio is increased by using two coupled inductors and switched capacitor circuit in both boost and buck operations. The proposed bidirectional converter in comparison with other presented high‐voltage gain boost converters with two coupled inductors in the literature has the highest voltage conversion ratio. In this study, the proposed topology is analysed in all operating modes and the current and voltage stresses of all switches, voltage gain and maximum and minimum current through the inductors are calculated for both boost and buck operations. Finally, the accuracy of the obtained analytical results and correct operation of the proposed converter are verified through PSCAD/EMTDC simulation and experimental results.